Venous thromboembolism after hip arthroscopy: a systematic review of incidence, risk factors, and international guidelines - Gao, Ting; Lv, Kai; Zhang, Hong; Chen, Jian; Zhao, Xiangde (Frontiers in Surgery, 2025)
PurposeThis review aims to systematically evaluate the incidence, risk factors, and international guideline discrepancies for venous thromboembolism (VTE) following hip arthroscopy (HA).MethodologyA search of four databases from the inception to April 20, 2025, identified studies reporting VTE outcomes post-HA. Relevant practice guideline recommendations were concurrently analyzed.ResultsTwenty-one studies encompassing 135,377 patients and five clinical guidelines were included. Female patients constituted 91,013 cases (67.2%). The mean patient age was 37.08 years; however, the average follow-up duration was limited to 3.7 months, which may be a study limitation. Pooled incidence rates were: deep vein thrombosis (DVT) 0.441%, pulmonary embolism (PE) 0.216%, and overall VTE 0.656%. The majority of studies were Level IV evidence (57%), with Level III evidence comprising 33%. Identified risk factors for post-HA VTE included obesity, oral contraceptive use, ≥45 years, overweight status, coagulopathy, and arteriovenous anomalies. The reported VTE incidence ranged from 0% to 6.94%. International guidelines vary, but most advocate for risk-stratified thromboprophylaxis.ConclusionsThe incidence of VTE following hip arthroscopy is low. Routine pharmacological thromboprophylaxis may not be necessary for standard-risk patients. However, high-risk individuals warrant personalized prophylaxis regimens, with pharmacological prophylaxis when clinically indicated based on risk assessment.